Fe Doped Titania Photocatalyst for Degradation of Methyl Orange. (2019) - Kanakaraju, Devagi; Hazim bin Ya, Muhamad; Akif Aizuddin bin Jasni, Muhamad; Sufian bin Endra, Mohammad; Lim, Ying-Chin
Abstract: Surface modification of titanium dioxide (TiO2 ) by doping method is one of the ways to lower TiO2 band gap and thus increasing its absorption to the visible region. This study was conducted to demonstrate a feasible modification of TiO2 by using iron (Fe) metal as the doping agent. Fe-doped TiO2 photocatalyst with the ratio of 1:1 was prepared by using the wet-impregnation method. The prepared photocatalyst was applied for the degradation of methyl orange (MO) under ultraviolet (UV) and visible light irradiation. A 0.20 g/L of Fe-doped TiO2 efficiently degraded 82.8% and 74.4% of 5 ppm MO under UV light and visible light irradiation, respectively. MO removal up to 85% was attained using bare TiO2 in the presence of UV compared to only 11% under visible light. The UV-Vis Diffuse Reflectance spectroscopy confirmed the reduction of TiO2 band gap upon Fe doping.